The London 2012 Summer Olympic Games: an analysis of usage of the Olympic Village `Polyclinic` by competing athletes - Vanhegan, I. S.; Palmer-Green, D.; Soligard, T.; Steffen, K.; O'Connor, P.; Bethapudi, S.; Budgett, R.; Haddad, F. S.; Engebretsen, L. (British Journal of Sports Medicine, 2013)
Background The London 2012 Summer Olympic Games involved 10 568 elite athletes representing 204 competing nations. To manage the varied healthcare needs of this diverse population, a Polyclinic was constructed in the athletes` village.Aim This work aims to summarise the usage of the Polyclinic by competing athletes and the facilities available to them.Methods All Polyclinic encounters were entered into a database from which data were exported for the time frame 28 July-12 August 2012, inclusive to cover the first to last full day of competition. Only Polyclinic data involving accredited athletes were analysed. All types of encounters were collected for analysis, not just sports-related issues.Results There were a total of 3220 encounters within the Polyclinic. This figure combines medical consultations, radiology/pathology investigations and prescriptions dispensed. Of these 3220 encounters, there were 2105 medical consultations; musculoskeletal comprised the greatest number (52%), followed by dental (30%) and ophthalmic (9%). The most frequently used imaging modality was MRI and diagnostic CT was used the least. After correction for multiple entries, Africa provided the largest proportion of athletes attending the Polyclinic (44%) and Europe the least (9%). Peak usage of all facilities was seen around days 9 and 10 of competition, reflecting the busiest time of the competition and the largest number of athletes in the village.Conclusions The Polyclinic managed a wide variety of both sports-related and non-sports-related injuries and illnesses. The breadth of specialists available for consultation was appropriate as was the ease of access to them. The radiology department was able to satisfy the demand, as were the pharmacy and pathology services. We would recommend a similar structure of facilities and available expertise in one clinic when planning future mass participation sporting events.